Sistem Informasi Diagnosa Penyakit Demam Berdarah Berbasis Web Dengan Metode Profile Matching (Studi Kasus : Puskesmas Kecamatan Cinere) - Meitasya Putri Kinanti; Yudi Kurniawan (CV. Multi Kreasi Media, 2023)
Dengue Hemorrhagic Fever (DHF) was first reported in Suarabaya in 1986. This DHF disease continues to increase and spread more widely. All regions of Indonesia are at risk of contracting this disease. Almost throughout the year, DHF is always found throughout Indonesia, especially at the beginning of the rainy season. In Indonesia, dengue fever has reached 17,877 cases in 34 provinces. From these data, there were 115 people who died. Symptoms experienced high fever that suddenly fluctuates up and down nausea to vomiting, flu, and dizziness. To overcome DHF, it is necessary to do early diagnosis. So that DHF can be prevented since the initial symptoms occur. This research uses the profile matching method which has been carried out a lot and got good results. This method was chosen because it produces decisions that are easy to understand. From this method a dengue fever diagnostic system application was made. This application can help people to predict dengue disease from an early age. Information System is a combination of information technology and the activities of people who use that technology to support operations and management. In a very broad sense, the term information system is often used to refer to interactions between people, algorithmic processes, data, and technology.